ONLINE IMPLEMENTATION OF HEALTH AND SPORTS PHYSICAL EDUCATION LEARNING IN JUNIOR HIGH SCHOOLS IN AIR WHITE SUB-DISTRICT, BATU BARA DISTRICT FOR ACADEMIC YEAR 2021/2022 - Afdillah, Ibnu; Damanik, Suryadi (Journal of Physical Education, Health and Sports Recreation, 2023)
This study aims to identify and analyze the implementation of online Physical Education, Sports and Health learning in junior high schools in Air Putih District, Batu Bara Regency for the 2021/2022 academic year. This research is a quantitative descriptive research and survey method. The sample in this study was 90 students, consisting of 3 schools, namely 30 students from SMP Negeri 1 Air Putih, 30 students from SMP Negeri 3 Air Putih, and 30 students. /i and Water Al Washliyah Private Middle School 6. This study has 9 indicators that are used as a reference for assessing the level of implementation of online Physical Education Sports and Health learning. The results of this study are: (1) Indicators of learning readiness, 83.78%; (2) Learning Material Suitability Indicators, 60.07%; (3) Learning Method Indicator, 82.59%; (4) Learning Media Indicators, 58.96%; (5) Material Mastery Indicator, 70.74%; (6) Learning Process Indicator, 70.67%; (7) System Indicators and Assessment Process, 79.56%; (8) Learning Constraints Indicator, 60%; (9) Learning Evaluation Indicator, 85.70%. Of the 9 indicators, it can be concluded that the level of implementation of online Physical Education, Sports and Health learning in junior high schools in Air Putih District, Batu Bara Regency is 72.45% in the good category.